Numerical simulation and simplified calculation method for heat exchange performance of dry air cooler in natural gas pipeline compressor station - Enbin Liu; Bingyan Guo; Liuxin Lv; Weibiao Qiao; Mohammadamin Azimi (Energy Science & Engineering, 2020)
Abstract In view of the complicated heat transfer calculation for air coolers and the difficulty of directly calculating the exit temperature of natural gas in a compressor station, taking the dry air cooler of model GP12 × 3‐6‐258‐13.0S‐S‐23.4/DR‐Ia configured in the West‐East Natural Gas Pipeline II as an example, a three‐dimensional simplified model of the air cooler is established. The model is used to simulate a temperature flow field of a dry air cooler‐finned tube based on Fluent flow field analysis software. This paper studies the cooling effect of the dry air cooler‐finned tube on high‐temperature and high‐pressure natural gas at compressor outlet. By comparing and analyzing the relationships among natural gas mass flow, inlet air temperature, inlet natural gas temperature, and outlet natural gas temperature for an air cooler, the formula of temperature drop of dry air cooler to natural gas is fitted, and the fitting formula is verified by field operation data. The results show that the average error between the fitting results and the actual data is less than 1.5%, which proves the correctness of the fitting formula and greatly simplifies the heat transfer calculation process for air coolers.